Prognostic impact of systolic blood pressure trajectory among patients hospitalised in an acute heart failure setting: insights from a real-world multinational cohort (Swiss Medical Weekly, 2026)
BACKGROUND: Systolic blood pressure is a prognostic marker in acute heart failure, but the prognostic implications of in-hospital changes in systolic blood pressure are unclear. We assessed the association between in-hospital systolic blood pressure changes and outcomes in a real-world, multinational cohort of acute heart failure patients.METHODS: We analysed consecutive patients hospitalised for acute heart failure between 2005 and 2020 at two tertiary-care centres (CHUV, Switzerland; NCCIM, Kyrgyzstan) with available systolic blood pressure measurements at admission and discharge. Patients were classified into four systolic blood pressure trajectory categories: stable normal/low (systolic blood pressure consistently